2020
DOI: 10.1017/s1047951120002413
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction in a child with multiple coronary aneurysms and neurofibromatosis type 1

Abstract: Vascular involvement in neurofibromatosis type 1 has been described, although coronary artery disease is rare. Data about clinical presentation and natural history are anecdotal. This is the first case of myocardial infarction due to coronary aneurysms in a 13-year-old boy with neurofibromatosis type 1. We discuss pathophysiology, diagnostic images, and therapeutic management of this rare association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Although NF1 patients have a well‐recognized predisposition for ACAD (Milewicz et al, 2010), its exact pathophysiology is not yet known, but could implicate a role for neurofibromin in endothelial dysfunction and smooth muscle cell migration and proliferation (Hamilton & Friedman, 2000; Milewicz et al, 2010). Molecular studies in patients with NF1 and ACAD have been identified both truncating (Ruggieri et al, 2000; present patient) and nontruncating (Isabelle et al, 2020; Konig et al, 2021) NF1 pathogenic variants. Although truncating mutations in NF1 have been associated with distinct vascular anomalies (Lasater et al, 2010), its specific correlation is limited because both types of mutations have been identified in patients with NF1 and ACAD (Table 1) and also, by the scarce number of reported individuals with available molecular study.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Although NF1 patients have a well‐recognized predisposition for ACAD (Milewicz et al, 2010), its exact pathophysiology is not yet known, but could implicate a role for neurofibromin in endothelial dysfunction and smooth muscle cell migration and proliferation (Hamilton & Friedman, 2000; Milewicz et al, 2010). Molecular studies in patients with NF1 and ACAD have been identified both truncating (Ruggieri et al, 2000; present patient) and nontruncating (Isabelle et al, 2020; Konig et al, 2021) NF1 pathogenic variants. Although truncating mutations in NF1 have been associated with distinct vascular anomalies (Lasater et al, 2010), its specific correlation is limited because both types of mutations have been identified in patients with NF1 and ACAD (Table 1) and also, by the scarce number of reported individuals with available molecular study.…”
Section: Discussionmentioning
confidence: 64%
“…From previous publications, we have summarized the characteristics of the 18 reported patients with NF1 and ACAD, including the patient reported here (Table 1). To the best of our knowledge, this is the first reported patient with NF1 and ACAD diagnosed at birth, since the previously reported youngest patients were adolescents of 13, 16, and 17 years old at diagnosis (Evrengul et al, 2013;Isabelle et al, 2020;Ruggieri et al, 2000), and the remainder were adults ranging from 22 to 80 years of age. The initial symptoms of ACAD were acute myocardial infarction in 11 of them and acute chest pain in two of them, respectively, and the other four patients were asymptomatic at diagnosis, like ours.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations